1998
DOI: 10.1111/j.1600-0447.1998.tb10049.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nordic Comparative Study on Sectorized Psychiatry: patients who use only psychiatric in‐patient care in comprehensive community‐based services — a 1‐year follow‐up study

Abstract: In the present paper a sample of patients using psychiatric in-patient care only is characterized and analysed with regard to characteristics of the psychiatric services. This paper forms part of the Nordic Comparative Study on Sectorized Psychiatry, designed to investigate contact rates and use of psychiatric care by new patients in 7 catchment areas in 4 Nordic countries during a 1-year follow-up. One-year treated incidence cohorts were used. The logistic regression analysis revealed that the variable 'psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Earlier research has found that difficulties in recruiting psychiatric healthcare staff [94] and distance to psychiatric healthcare [95] can explain higher psychiatric morbidity in rural areas. Large differences in the availability and utilization of mental healthcare services can influence the rates of psychiatric morbidity and thereby differences in psychiatric morbidity between regions [96].…”
Section: The Determinants Of Regional Variations In Direct Costs and mentioning
confidence: 99%
“…Earlier research has found that difficulties in recruiting psychiatric healthcare staff [94] and distance to psychiatric healthcare [95] can explain higher psychiatric morbidity in rural areas. Large differences in the availability and utilization of mental healthcare services can influence the rates of psychiatric morbidity and thereby differences in psychiatric morbidity between regions [96].…”
Section: The Determinants Of Regional Variations In Direct Costs and mentioning
confidence: 99%
“…Regarding utilisation parameters, such as emergency admissions to inpatient care (Saarento et al, 1998a), proportion of patients who use only inpatient care. (Saarento et al, 1998b), emergency outpatient contacts (Saarento et al, 1998c), median length of stay (0iesvold et al, 1999) and readmissions (0iesvold et al, 2000), there were no significant differences between urban and rural areas.…”
Section: The Present Services In Northern Norwaymentioning
confidence: 96%
“…Tyrer et al [19] compared the clinical outcome and costs of care of psychiatric patients in London allocated to community-based multidisciplinary teams or to hospital-based outpatient care programmes after discharge from inpatient care; the clinical outcomes were similar but admission to hospital during follow-up was more likely in the hospital-based care group. In general, lack of 24-hour emergency settings correlates positively with the use of inpatient care alone [20] . It indicates that the extended availability of outpatient services in the community for people in crisis may facilitate the comprehensive utilization of mental health services [8] .…”
Section: Evaluation Of Ambulatory Care Settings In Psychiatrymentioning
confidence: 99%